A matched pair analysis of multicenter longterm follow‐up after split‐liver transplantation with extended right grafts. Issue 11 (26th October 2017) - Ross, Michael W.; Cescon, Matteo; Angelico, Roberta; Andorno, Enzo; Rossi, Giorgio; Pinna, Antonio; De Carlis, Luciano; Baccarani, Umberto; Cillo, Umberto; Colledan, Michele; Mazzaferro, Vincenzo; Tisone, Giuseppe; et al.
Abstract : Split‐liver transplantation has been proposed as an alternative to whole liver (WL) transplantation to expand the donor pool, but studies comparing adult longterm outcomes between the 2 methods are conflicting and limited. This is the first Italian multicenter study that retrospectively analyzed 119 matched‐pair recipients of whole and extended right grafts (ERGs) for longterm survival outcomes. In the overall population, WL recipients showed higher patient survival at 1 (93% versus 73%), 5 (87% versus 65%), and 10 years (83% versus 60%) after transplantation compared with split‐liver recipients ( P  < 0.001); graft survivals of WL recipients were also superior at 1 (90% versus 76%), 5 (84% versus 57%), and 10 years (81% versus 52%) posttransplant ( P  < 0.001). However, among the 81 matched pairs that survived the first posttransplant year, 5‐ and 10‐year patient survivals were 90% and 81% for split recipients and 99% and 96% for whole recipients, respectively ( P  = 0.34). The 5‐ and 10‐year graft survivals were also comparable: 87% and 77% for split recipients, and 86% and 82% for whole recipients ( P  = 0.86). Cox regression analysis identified donor age >50, donor‐to‐recipient weight ratio < 1, retransplantation status, and United Network for Organ Sharing I‐IIA status as risk factors for partial graft use. There were no significant differences in 5‐year outcomes based on center volume. In conclusion, we demonstrate that adult liver transplantation with ERGs can achieve longterm success comparable with that of whole grafts in appropriate patients but should be selectively used in patients with risk factors. Liver Transplantation 23 1384–1395 2017 AASLD.